Proceedings of the 36th International ACM SIGIR Conference on Research and Development in Information Retrieval 2013
DOI: 10.1145/2484028.2484069
|View full text |Cite
|
Sign up to set email alerts
|

Task-aware query recommendation

Abstract: When generating query recommendations for a user, a natural approach is to try and leverage not only the user's most recently submitted query, or reference query, but also information about the current search context, such as the user's recent search interactions. We focus on two important classes of queries that make up search contexts: those that address the same information need as the reference query (on-task queries), and those that do not (off-task queries). We analyze the effects on query recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Some approaches, such as pseudo-relevance feedback [13] and query expansion [30] focus on improving IR systems and algorithms. Others try to improve users' experience by o↵ering related queries [2] or making personalized recommendations [29]. In the end, the e↵ectiveness of an IR setting has to do with user's preferences and/or skills just as much as it has with system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches, such as pseudo-relevance feedback [13] and query expansion [30] focus on improving IR systems and algorithms. Others try to improve users' experience by o↵ering related queries [2] or making personalized recommendations [29]. In the end, the e↵ectiveness of an IR setting has to do with user's preferences and/or skills just as much as it has with system performance.…”
Section: Introductionmentioning
confidence: 99%
“…No difference in session success was found between those using the feedback and those not using it, but those using it did continue to employ it effectively on an ongoing basis. A number of recent studies have shown that search tasks provide a rich context for performing log-based query suggestion [64,111,128], underscoring the importance of studying query reformulation in search tasks.…”
Section: Query Reformulation and Refinementmentioning
confidence: 99%
“…Increasingly, these IR systems are able to leverage insights about the context of an information need beyond or even before an expressed query. In such a pro-active search scenario, the context may be given by a user's location [22] or activities [60,64,128]. These new interaction scenarios signal a move from pulling to pushing information, accelerated by constant access to the web on smart phones and tablets.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that people may be involved in off-topic tasks while working on one-topic tasks (Feild & Allan, 2013), where search is a changing process that combines keyword search, browsing, and serendipity or unintentional discovery (Jiang, He, & Allan, 2014), in addition to impulse purchasing triggered by advertisement banners and promotions that are common in product search activities.…”
Section: Research Papermentioning
confidence: 99%